Inheritance and correlation of nucleic acid pyrimidine bases. Issue 20 (22nd May 2013) - Yang, Zejin; Duffy, Patrick; Wang, Feng
<x xml:space="preserve">Abstract</x> Valence electronic structures of pyrimidine (P, C4N2H4) and nucleic acid (NA) pyrimidine bases, including cytosine (C, C4N3OH5), thymine (T, C5N2O2H6), and uracil (U, C4N2O2H4), are studied using B3LYP/aug‐cc‐pVTZ, B3LYP/TZVP, SAOP/et‐pVQZ, and OVGF/TZVP. The highest occupied molecular orbital (HOMO) and the next HOMO (NHOMO) of pyrimidine are conclusively assigned as 7b2 and 2b1, respectively. The ionization energy spectra and valence orbital momentum distributions studies reveal that the NA bases, that is, cytosine, thymine, and uracil, exhibit a larger degree of similarity to each other than to pyrimidine, although they do inherit certain properties from pyrimidine. © 2013 Wiley Periodicals, Inc.